On a complete topological inverse polycyclic monoid - Bardyla, S.O.; Gutik, O.V. (Carpathian Mathematical Publications, 2016)
We give sufficient conditions when a topological inverse $λ$-polycyclic monoid $P_{λ}$ is absolutely $H$-closed in the class of topological inverse semigroups. For every infinite cardinal $λ$ we construct the coarsest semigroup inverse topology $τ_{mi}$ on $P_λ$ and give an example of a topological inverse monoid $S$ which contains the polycyclic monoid $P_2$ as a dense discrete subsemigroup.